Synthesis, crystal structures and magnetic properties of composites incorporating an Fe(II) spin crossover complex and polyoxometalates - Kuramochi, Satoshi; Shiga, Takuya; Cameron, Jamie M.; Newton, Graham N.; Oshio, Hiroki (MDPI, 2017)
[Fe(dppOH)2]2+ (dppOH = 2,6-di(pyrazol-1-yl)-4-(hydroxymethyl)pyridine) is known to show spin crossover (SCO) behavior and light-induced excited spin state transitions (LIESST). Here, we show that the SCO properties of the [Fe(dppOH)2]2+ complex can be altered by a crystal engineering approach employing counter anion exchange with polyoxometalate (POM) anions. Using this strategy, two new composite materials: (TBA)[Fe(dppOH)2][PMo12O40] (1) and [Fe(dppOH)2]3[PMo12O40]2 (2) (TBA = tetra-n-butylammonium) have been isolated and studied by single crystal X-ray diffraction and magnetic susceptibility measurements. 1 is found to be in a high spin state at 300 K and shows no spin crossover behavior due to a dense packing structure induced by hydrogen bonding between the hydroxyl group of the dppOH ligands and the POM anions. Conversely, 2 contains two crystallographically unique Fe centers, where one is in the low spin state whilst the other is locked in a high spin state in a manner analogous to 1. As a result, 2 is found to show partial spin crossover behavior around 230 K with a decrease in the χmT value of 1.9 emu·mol−1·K. This simple approach could therefore provide a useful method to aid in the design of next generation spin crossover materials.